Observational data on the reproductive condition of female Oceania fantail rays, Taeniura lessoni, from Drawaqa Island, Fiji - Glaus, Kerstin; Vierus, Tom; Macfarlane, Robert (Frontiers in Marine Science, 2024)
Data on the reproductive biology of elasmobranchs are essential for understanding their life history. Published studies on batoid ray reproductive biology are comparatively scarce, leading to limited understanding and data gaps. The Oceania fantail ray, Taeniura lessoni, is a good example. This Data Deficient nearshore stingray is restricted to Melanesia, with lacking biological and ecological data, including reproduction. To expand upon the limited life-history data for this species, this short paper provides observational data on the reproductive condition in female T. lessoni, at Drawaqa Island, Fiji. Field work involved direct observations and ocean temperature measurements. Over 40 days spanning three months, 105 surveys were conducted across five sites, resulting in 71 sightings of the species. Based on spot patterns and body markings, four female individuals were identified. Between January and March 2024, these females exhibited convex dorsa indicating advanced gestation, transitioning to concave dorsa suggesting parturition. The presence of neonates from early March onwards coincided with the estimated parturition period inferred from the rays' condition. Furthermore, a female previously pregnant was photographed with a dermal abrasion around her pectoral fin, possibly indicating pre-copulatory biting, suggesting a continuous reproductive cycle. The average monthly water temperature at the surveyed sites remained relatively stable throughout the study. Collectively, our findings suggest that Drawaqa Island provides suitable habitat niches for reproductive activities in female T. lessoni. Repeated and long-term data is certainly needed to confirm either a continuous reproductive cycle or seasonal peaks. While preliminary, our observational data represents the first documentation on female reproductive condition in a stingray in Fiji.